New-Onset Cervical Lymphadenopathy in a Patient Undergoing Treatment of Pulmonary Mycobacterium avium Complex Infection: Toxoplasmosis Lymphadenitis - Chia-Yu Chiu; Amara Sarwal; Peter Yangga; Dasol Kang; Addi Feinstein (Case Reports in Infectious Diseases)
Immunocompetent hosts with toxoplasmosis are usually asymptomatic. However, T. gondii can present as an acute systemic infection. Symptomatic patients usually have a benign, self-limited course that typically lasts from a few weeks to months. Herein, we present a 66-year-old immunocompetent female who developed dysphagia and new-onset cervical lymphadenopathy during pulmonary Mycobacterium avium complex treatment.